2021
DOI: 10.5194/nhess-21-3421-2021
|View full text |Cite
|
Sign up to set email alerts
|

Investigating causal factors of shallow landslides in grassland regions of Switzerland

Abstract: Abstract. Mountainous grassland slopes can be severely affected by soil erosion, among which shallow landslides are a crucial process, indicating instability of slopes. We determine the locations of shallow landslides across different sites to better understand regional differences and to identify their triggering causal factors. Ten sites across Switzerland located in the Alps (eight sites), in foothill regions (one site) and the Jura Mountains (one site) were selected for statistical evaluations. For the sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…This shows parallels to models aiming to predict soil depth in general based on geomorphology (Catani et al, 2010;Xiao et al, 2023). There is also a notable overlap with variables that Zweifel et al (2021) identified as important causal factors of shallow landslides in grassland regions of Switzerland. In addition, the inclusion of the lithology by proxy of the mean local density of the underlying bedrock and the inclusion of the vegetation (especially the forest) through the maximum of the VHM is also worth mentioning.…”
Section: Covariate Selectionmentioning
confidence: 66%
“…This shows parallels to models aiming to predict soil depth in general based on geomorphology (Catani et al, 2010;Xiao et al, 2023). There is also a notable overlap with variables that Zweifel et al (2021) identified as important causal factors of shallow landslides in grassland regions of Switzerland. In addition, the inclusion of the lithology by proxy of the mean local density of the underlying bedrock and the inclusion of the vegetation (especially the forest) through the maximum of the VHM is also worth mentioning.…”
Section: Covariate Selectionmentioning
confidence: 66%
“…This shows parallels to models aiming to predict soil depth in general based on geomorphology (Catani et al, 2010;Xiao et al, 2023). There is also a notable overlap with variables that Zweifel et al (2021) identified as important causal factors of shallow landslides in grassland regions of Switzerland. In addition, the inclusion of the lithology by proxy of the mean local density of the underlying bedrock and the inclusion of the vegetation (especially the forest) through the maximum of the VHM is also worth mentioning.…”
Section: Covariate Selectionmentioning
confidence: 66%